Formulation optimization of floating microbeads containingmodified Chinese yam starch using factorial design. (2012)
Controlled release floating metformin hydrochloride microbeads were prepared and optimized using a blend of varying concentrations of freeze-dried pregelatinized Chinese yam starch (Dioscorea oppositifolia L) and sodium alginate. Floating microbeads were prepared by the ionotropic gelation method using 10% w/v calcium chloride as the cross-linking agent and sodium bicarbonate as the gas releasing agent. A full 32 factorial design was used to investigate the influence of two variables: concentrations of starch (X1) and sodium bicarbonate (X2) on the swelling, floating lag time and amount of drug released after 1 hour (Q1) and 10 hours (Q10). Potential variables such as the concentrations of drug and total polymer were kept constant. The results showed that the properties of the floating microbeads were significantly (p<0.01) affected by the concentration of the modified Chinese yam starch. Buoyancy and drug release appeared to be facilitated by increased concentrations of both starch and sodium bicarbonate in the formulation. The results also show that an optimized formulation of metformin hydrochloride could be obtained with the potential for gastroretentive controlled drug delivery using a blend of freeze-dried pregelatinized Chinese yam starch and sodium alginate.